UJI ANTIBAKTERI DAN MODIFIKASI HIDROKSIAPATIT DARI LIMBAH KERABANG TELUR BEBEK (A. platyrhynchos javanica) - Agung Rimayanto Gintu; Elizabeth Betty Elok Kristiani; Yohanes Martono (UIN Sunan Gunung Djati Bandung, 2023)
Hydroxyapatite (HAp) was one of synthetic compounds synthesized from raw materials like eggshells, HAp initiated to applied in toothpaste formulations as active compounds role as abrasives, remineralitation agents and antibacteries against caries. The aim of this study was to measured the antibacterial activity of HAp synthesized from Local Duck (A. platyrhynchos javanica) eggshells against 4 species of caries bacteries: S. mutans, L. acidophyllus, N. asteroides and N. asteroides. The concentration of HAp separated into 3 levels: 100, 500 and 1000ppm, the antibacterial activity of HAp only produced against L. acidophyllus at 1000ppm concentration of HAp, the diameter of inhibitory showed 5,19 ± 0,0203mm, this activity belongs to weak activity then need to modified the HAp to increasing the antibacterial activity. The HAp modificated by Mix and Doped. The strongest antibacterial showed by Silver (Ag) doped, with diameter of inhibitory against 4 caries bacteries sequentaly 17,91 ± 0,1723mm; 23,10 ± 0,0361mm; 19,06 ± 0,0348mm; and 19,12 ± 0,0493mm; those modifications increating the antibacterial from weak to strong and very strong range.